Hif‐1alpha stabilisation is protective against infection in zebrafish comorbid models. (18th June 2020) - Schild, Yves; Mohamed, Abdirizak; Wootton, Edward J.; Lewis, Amy; Elks, Philip M.
Abstract : Multi‐drug‐resistant tuberculosis is a worldwide problem, and there is an urgent need for host‐derived therapeutic targets, circumventing emerging drug resistance. We have previously shown that hypoxia‐inducible factor‐1α (Hif‐1α) stabilisation helps the host to clear mycobacterial infection via neutrophil activation. However, Hif‐1α stabilisation has also been implicated in chronic inflammatory diseases caused by prolonged neutrophilic inflammation. Comorbid infection and inflammation can be found together in disease settings, and it remains unclear whether Hif‐1α stabilisation would be beneficial in a holistic disease setting. Here, we set out to understand the effects of Hif‐1α on neutrophil behaviour in a comorbid setting by combining two well‐characterised in vivo zebrafish models – TB infection ( Mycobacterium marinum infection) and sterile injury (tailfin transection). Using a local Mm infection near to the tailfin wound site caused neutrophil migration between the two sites that was reduced during Hif‐1α stabilisation. During systemic Mm infection, wounding leads to increased infection burden, but the protective effect of Hif‐1α stabilisation remains. Our data indicate that Hif‐1α stabilisation alters neutrophil migration dynamics between comorbid sites and that the protective effect of Hif‐1α against Mm is maintained in the presence of inflammation, highlighting its potential as a host‐derived target against TB infection. Abstract : Using comorbid zebrafish models of Mycobacterium marinum (Mm) infection and tailfin wound‐induced inflammation, we show that stabilisation of hypoxia‐inducible factor‐1α (Hif‐1α) is protective against systemic infection, despite comorbid inflammation leading to increased infection. Using a local infection, we show that neutrophils distribute between infection and tailfin wound sites, but that Hif‐1α stabilisation caused neutrophils migration between the two sites to be reduced, increasing numbers at the infection.